Software – defined networking based secure rout-ing in mobile ad hoc network - Prasad, B. V. V. S.; Salman Ali, Sd. (International Journal of Engineering and Technology, 2017)
Traditional communication networks can be leveraged by separating controlling functions from forwarding functions using emerging technology known as Software Defined Networking (SDN). Though SDN has been around for some years, it was mostly limited to wired networks. Of late, it is being adapted to wireless networks. The programmable interface with decoupled controller can be used with MANET to integrate with other networks besides controlling it well. Both control and security are inevitable for the successful implementation of SDN in wireless networks. Towards this end, in this paper we implemented SDN based MANET for secure routing. Open Flow is used for implementing SDN controller while IDC is used for securing communications. Our framework is evaluated with NS3 simulations that reveal significant performance improvement when compared with traditional ad hoc networks that do not use SDN. This is achieved as SDN controller can quickly adapt to changed topologies due to node mobility.